Exploring speech acts in the Treasure Island novel: A pragmatic approach - Nurjannah Nurjannah (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2025)
The research aims to identify the types of speech acts found in the dialogue in the Treasure Island novel. This research was conducted with the help of Searle’s theory of speech acts (1975). A descriptive qualitative method was used in this research. The data in this research are in the form of dialogue among the characters in the novel. The data collection involved reading and identifying relevant dialogue that was recorded and analyzed based on speech act classification. Then, the data were analyzed by Searle’s theory into the five types. Based on the discussion, the researcher identified four types in the novel: directive, representative, expressive, and commissive. The speech acts uttered by characters in the novel are conveyed in both literal and non-literal ways. This analysis demonstrates that understanding speech acts enhances the interpretation of character interactions and the overall meaning of the text. The implication of the study is to become proficient in pragmatics, particularly in the theory of speech actions, to comprehend the speaker’s goal and ensure that the communication is realized.